Enhanced dechlorination for multi-source solid wastes using gas-pressurized torrefaction and its removal mechanism - Fu, Jia; Yi, Linlin; Li, Kaiyuan; Zhang, Yan; Zhang, Tong; Li, Aijun; Wang, Tianrun; Zou, Yanyan; Li, Xian; Yao, Hong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •A high-efficiency and low-energy pre-dechlorination method was innovatively proposed.•Migration behavior of chlorine during gas-pressure torrefaction was unraveled.•Gas pressure and secondary reactions synergistically enhance the dechlorination.•GP-torrefaction enhanced the autocatalytic reaction of HCl, especially in PVC.•Chlorinated pollutants were significantly reduced during GP semi-char incineration. The emission of chlorinated pollutants from the thermal disposal of multi-source solid waste (MSW) incineration has posed significant hazards, garnering widespread concern. The study proposed a novel pre-dechlorination technology for MSW through gas-pressurized (GP) torrefaction without external pressurization. Typical chlorinated wastes, such as polyvinyl chloride (PVC), neoprene rubber (NR) and corn straw (CS), were selected. The study focused on two aspects: the pre-dechlorination effect of GP-torrefaction at 225–325 °C for each solid waste; the release of chloride during subsequent incineration utilization of semi-chars. Results showed that the GP-torrefaction had superior dechlorination efficiency than atmospheric (AP) torrefaction. For organic-Cl sources (PVC, NR), the dechlorination efficiency of GP-torrefaction for PVC reached up to 73.9–87.7 wt% at 225–275 °C, which was 23.79–60.17 wt% higher than AP-torrefaction. The efficiency for NR was 10.27–23.15 wt% higher than AP-torrefaction at 300–325 °C. Significantly, the autocatalytic reactions of HCl played an important role in dechlorination of PVC. And the CC–Cl structure in NR were substantially converted into allyl chlorides (C–C–Cl), which were easier to dechlorination. For inorganic-Cl source (CS), GP-torrefaction enhanced the decomposition of cellulose and lignin. The abundant oxygen-containing functional groups derived from the decomposition can react with Inorg-Cl to facilitate the release of HCl/CH3Cl at 225–275 °C. Moreover, a portion of char-Cl (8.2–86.1 wt%) was derived from the secondary adsorption of HCl on three materials. It could be easily further removed by water-washing. In the incineration utilization, the chlorides content in the flue gas was only 1.29–2.69 % for three materials, and the HCl content being negligible for NR and CS. Overall, GP-torrefaction is a novel and effective method to reduce chlorinated pollution, providing new insights for the low consumption and efficient utilization of MSW.